A Clinical Study Of The Method Of Early Diagnosis Of Coronary Heart Disease (Eurasian Medical Research Periodical, 2025)
Recently, the issue of early diagnosis of coronary heart disease (CHD) remains the most urgent task of cardiology. The gas analytical method for the analysis of exhaled air (EA) is a new approach to solving this problem [1,5,11]. Our clinical studies of this technique, used to develop a non-invasive method for the diagnosis of coronary heart disease, have led to the following main results: CHD is accompanied by impaired metabolism of biogenic amines [6], volatile biogenic amines are found in the composition of explosives in patients with CHD [1, 2], the content of diethylamine in explosives increases most significantly in patients with postinfarction cardiosclerosis (PICS) [7], secondary amines (SA) can be formed as a result of the reduction of Schiff bases (SHO) under acidosis conditions in the cellular sarcosomes of the cardiac muscle [8,9]. However, the nature of the dependence of the kinetic parameters of SA formation on the degree and scale of ischemic myocardial zones remains unclear.